Retail deposit fees and multimarket banking - Hannan, Timothy H. (Journal of Banking & Finance, 2006)
This paper reports a systematic examination of the determinants of deposit-related retail banking fees using a set of survey data that is unusual for its size, specificity, and sampling properties. The analysis focuses explicitly on six different fees associated with checking accounts and automated teller machine (ATM) usage. A preliminary analysis documents that, on average, multimarket banks charge substantially higher fees than do typically smaller, single-market banks. A more detailed econometric analysis yields results consistent with predictions of recent models. In particular, it finds that the greater the presence of multimarket banks in the local market, the higher are the retail deposit fees of single-market banks (except in highly concentrated markets) and the weaker is the positive relationship between those fees and market concentration.